INDONESIAN EFL TEACHERS’ PERSPECTIVE ON GOVERNMENT PROFESSIONAL DEVELOPMENT PROGRAM - Diah Safithri Armin (VISION, 2020)
Indonesian government provides many programs in developing teacher’s profession, such as certification, standard of education background, and teachers’ group (Teacher Activity Center (PKG), Course Teacher Forum (MGMP), and Teacher Working Group (KKG)). This study attempted to investigate teachers’ perspective on government professional development programs. This research applied basic interpretive qualitative research, and used open-ended questionnaire and semi structured interview as technique of collecting data. The participants of this research were fifty EFL teachers from five cities in Indonesia. The research finding showed that Indonesian EFL teachers have positive perspective on professional development in improving their teaching skill. Most of the EFL teachers also have positive perspective on government professional development programs, even though some of them suggest that the government professional development program is better to provide activities improving their teaching skills than to discuss administration. The implication of this study is the Indonesian EFL teachers have positive perspective on government professional development programs, but they also suggest the government professional development programs should focus on helping the teacher in improving their teaching skills.